Discovering antecedents of antisocial behavior in the classroom: the influence of social exclusion on antisocial risk-taking - Corinna Lorenz; Philipp Nicolay; Corinna Hank; Christian Huber; Nicola K. Ferdinand (Frontiers in Psychology)
Introduction/BackgroundThis study investigates how social exclusion experiences influence antisocial risk-taking behaviors in adolescents by examining the interplay between classroom social acceptance and experimentally induced social exclusion.MethodsUsing a sequential experimental design with students in years 7–9 of the German school system (ages 12–16), we first assessed participants’ classroom social acceptance within their classrooms through sociometric measures, then randomly assigned them to experience either experimentally induced social inclusion (n = 65) or exclusion (n = 64) using the Cyberball paradigm, and finally measured their antisocial risk-taking using an adapted Columbia Card Task as well as moral disengagement.ResultsResults revealed a complex relationship whereby social exclusion effects were moderated by pre-existing classroom social acceptance status. Well-integrated adolescents responded to exclusion by reducing antisocial risk-taking when potential harm to others was high, while poorly integrated adolescents demonstrated the opposite pattern, increasing risky choices that could harm others. Our exploratory analysis further indicated that moral disengagement was positively associated with antisocial risk-taking and negatively correlated with classroom social acceptance, particularly among excluded adolescents.Discussion/ConclusionsThese findings suggest that responses to social exclusion are not uniform but depend critically on adolescents’ established social status, contributing to our understanding of the cognitive and social factors that shape decision-making in antisocial contexts during this developmental period.